Facile Synthesis of Ligand-Free Iridium Nanoparticles and Their In Vitro Biocompatibility - Anna L. Brown; Hayden Winter; Andrea M. Goforth; Gaurav Sahay; Conroy Sun (Nanoscale Research Letters, 2018)
Abstract High-density inorganic nanoparticles have shown promise in medical applications that utilize radiation including X-ray imaging and as radiation dose enhancers for radiotherapy. We have developed an aqueous synthetic method to produce small (~ 2 nm) iridium nanoparticles (IrNPs) by reduction of iridium(III) chloride using a borohydride reducing agent. Unlike other solution-based synthesis methods, uniform and monodispersed IrNPs are produced without the use of surfactants or other solubilizing ligands. These nanoparticles are highly crystalline as observed by X-ray diffraction and high-resolution transmission electron microscopy (TEM). In vitro metabolic toxicity assays using hepatocyte and macrophage cells demonstrate that both IrNPs and iridium(III) chloride are well tolerated at concentrations of up to 10 μM iridium. Furthermore, the IrNPs were assessed in a hemolytic assay and found to have no significant impact on red blood cells when exposed to concentrations up to 100 μM. Overall, these results support the potential for the in vivo application of this nanomaterial.